name | natural-even-odd |
version | 1.0 |
description | Definitions and theorems about natural number even and odd |
author | Joe Hurd <joe@gilith.com> |
license | MIT |
show | Data.Bool Number.Natural Number.Numeral |
⊦ ∀n. even n ∨ odd n
⊦ ∀n. ¬(even n ∧ odd n)
⊦ ∀n. even (2 * n)
⊦ ∀n. ¬even n ⇔ odd n
⊦ ∀n. ¬odd n ⇔ even n
⊦ ∀n. odd (suc (2 * n))
⊦ ∀m n. even (m * n) ⇔ even m ∨ even n
⊦ ∀m n. even (m + n) ⇔ even m ⇔ even n
⊦ ∀m n. odd (m * n) ⇔ odd m ∧ odd n
⊦ ∀n. even n ⇔ ∃m. n = 2 * m
⊦ (even 0 ⇔ T) ∧ ∀n. even (suc n) ⇔ ¬even n
⊦ (odd 0 ⇔ F) ∧ ∀n. odd (suc n) ⇔ ¬odd n
⊦ ∀m n. odd (m + n) ⇔ ¬(odd m ⇔ odd n)
⊦ ∀m n. odd (exp m n) ⇔ odd m ∨ n = 0
⊦ ∀n. odd n ⇔ ∃m. n = suc (2 * m)
⊦ ∀m n. even (exp m n) ⇔ even m ∧ ¬(n = 0)
⊦ ∀n. (∃k m. odd m ∧ n = exp 2 k * m) ⇔ ¬(n = 0)
⊦ ∀n. (even n ⇒ ∃m. n = 2 * m) ∧ (¬even n ⇒ ∃m. n = suc (2 * m))
⊦ T
⊦ F ⇔ ∀p. p
⊦ 1 = suc 0
⊦ ∀t. t ∨ ¬t
⊦ (¬) = λp. p ⇒ F
⊦ (∃) = λP. P ((select) P)
⊦ ∀t. (∀x. t) ⇔ t
⊦ ∀t. (∃x. t) ⇔ t
⊦ ∀t. (λx. t x) = t
⊦ (∀) = λP. P = λx. T
⊦ ∀x. x = x ⇔ T
⊦ ∀n. ¬(suc n = 0)
⊦ 2 = suc 1
⊦ ∀n. bit0 n = n + n
⊦ (⇒) = λp q. p ∧ q ⇔ p
⊦ ∀t. (t ⇔ T) ∨ (t ⇔ F)
⊦ ∀n. bit1 n = suc (n + n)
⊦ (¬T ⇔ F) ∧ (¬F ⇔ T)
⊦ ∀t1 t2. t1 ∨ t2 ⇔ t2 ∨ t1
⊦ ∀n. 2 * n = n + n
⊦ (∧) = λp q. (λf. f p q) = λf. f T T
⊦ ∀P. ¬(∃x. P x) ⇔ ∀x. ¬P x
⊦ (∃) = λP. ∀q. (∀x. P x ⇒ q) ⇒ q
⊦ (∨) = λp q. ∀r. (p ⇒ r) ⇒ (q ⇒ r) ⇒ r
⊦ ∀P. (∃x y. P x y) ⇔ ∃y x. P x y
⊦ ∀P Q. P ∨ (∃x. Q x) ⇔ ∃x. P ∨ Q x
⊦ ∀P Q. (∃x. P x) ∧ Q ⇔ ∃x. P x ∧ Q
⊦ ∀P Q. (∃x. P x) ∨ Q ⇔ ∃x. P x ∨ Q
⊦ ∀m n p. m * (n * p) = m * n * p
⊦ ∀P. (∀x. ∃y. P x y) ⇔ ∃y. ∀x. P x (y x)
⊦ ∀m n. m * n = 0 ⇔ m = 0 ∨ n = 0
⊦ ∀P. P 0 ∧ (∀n. P n ⇒ P (suc n)) ⇒ ∀n. P n
⊦ (∀t. ¬¬t ⇔ t) ∧ (¬T ⇔ F) ∧ (¬F ⇔ T)
⊦ ∀m n. exp m n = 0 ⇔ m = 0 ∧ ¬(n = 0)
⊦ ∀P. (∀n. (∀m. m < n ⇒ P m) ⇒ P n) ⇒ ∀n. P n
⊦ ∀P Q. (∀x. P x ∧ Q x) ⇔ (∀x. P x) ∧ ∀x. Q x
⊦ ∀P Q. (∀x. P x ⇒ Q x) ⇒ (∃x. P x) ⇒ ∃x. Q x
⊦ ∀e f. ∃fn. fn 0 = e ∧ ∀n. fn (suc n) = f (fn n) n
⊦ ∀m n p. m * p < n * p ⇔ m < n ∧ ¬(p = 0)
⊦ (∀m. exp m 0 = 1) ∧ ∀m n. exp m (suc n) = m * exp m n
⊦ (∀m. m < 0 ⇔ F) ∧ ∀m n. m < suc n ⇔ m = n ∨ m < n
⊦ ∀t. ((T ⇔ t) ⇔ t) ∧ ((t ⇔ T) ⇔ t) ∧ ((F ⇔ t) ⇔ ¬t) ∧ ((t ⇔ F) ⇔ ¬t)
⊦ ∀t. (T ∧ t ⇔ t) ∧ (t ∧ T ⇔ t) ∧ (F ∧ t ⇔ F) ∧ (t ∧ F ⇔ F) ∧ (t ∧ t ⇔ t)
⊦ ∀t. (T ∨ t ⇔ T) ∧ (t ∨ T ⇔ T) ∧ (F ∨ t ⇔ t) ∧ (t ∨ F ⇔ t) ∧ (t ∨ t ⇔ t)
⊦ ∀t. (T ⇒ t ⇔ t) ∧ (t ⇒ T ⇔ T) ∧ (F ⇒ t ⇔ T) ∧ (t ⇒ t ⇔ T) ∧ (t ⇒ F ⇔ ¬t)
⊦ (∀n. 0 + n = n) ∧ (∀m. m + 0 = m) ∧ (∀m n. suc m + n = suc (m + n)) ∧
∀m n. m + suc n = suc (m + n)
⊦ ∀p q r.
(p ∨ q ⇔ q ∨ p) ∧ ((p ∨ q) ∨ r ⇔ p ∨ q ∨ r) ∧ (p ∨ q ∨ r ⇔ q ∨ p ∨ r) ∧
(p ∨ p ⇔ p) ∧ (p ∨ p ∨ q ⇔ p ∨ q)
⊦ (∀n. 0 * n = 0) ∧ (∀m. m * 0 = 0) ∧ (∀n. 1 * n = n) ∧ (∀m. m * 1 = m) ∧
(∀m n. suc m * n = m * n + n) ∧ ∀m n. m * suc n = m + m * n